Dual-purpose concrete domes: A strategy for the revival of thin concrete shell roofs. (December 2020) - Zingoni, Alphose; Enoma, Nosakhare
Abstract: The use of thin concrete shells as long-span roofing solutions has declined over the past 60 years, largely as a result of the expensive nature of the formwork for curved surfaces, and the stiff competition from other more economical options such as steel space grids. The purpose of this contribution is to explore the simultaneous use of thin concrete shells for roofing and liquid-containment purposes. It is hoped the concept of dual-purpose concrete shells will provide enhanced justification for the higher costs associated with the construction of curved surfaces, thereby helping to revive the widespread use of elegant thin concrete shells once again. Specifically, the state of stress in various dual-purpose configurations is evaluated, and the effect of varying shell thickness in critical zones is investigated, allowing some preliminary insights to be gained. With appropriate thickness enhancement in the critical zones, the concept appears feasible, but before firm conclusions can be made, detailed buckling studies need to be undertaken.